Response to John G. Brock-Utne. Comment on Hurley, J.C. Towards Clinical Application of Anti-endotoxin Antibodies; A Re-Appraisal of the Disconnect - James C. Hurley (Toxins, 2014)
I appreciate the thoughtful comments from Dr. Brock-Utne [1] on my recent review of the disconnect between animal studies and clinical experience with anti-endotoxemia therapies [2].